Detection of Some Virulence Factors Genes in S. Aureus Isolated From Different Clinical Cases - Rawaa M. Mohammed (Journal of Global Pharma Technology, 2019)
A total of 60 specimens (urine, burn swabs, and wound swabs) from different clinical cases were collected from patients (in different age groups) who admitted to several health centers in Al-Dewaniya General Teaching Hospital, during a period extending from October 2016 to January 2017. Some virulence factors was investigated for 30 isolates only of MRSA using Single and Multiplex PCR For detection virulence factor genes which both coa gene encoding production of coagulase, clfA gene encoding for clumping factor, spa gene encoding for protein A, fnbA gene encoding for fibronectin binding proteins, luks gene encoding production of Panton Valentine Leukocidin (PVL), Results showed that all 30 isolates (100%) were possescoa, clfA, spaand fnbA genes, 13 (43.3%) were possesluks gene. Nanoparticle represented by gold and silver were tested in this study to defect their effect on viability of S.aureus. The results indicated that? Particle were more effective to inhibit the grow that of this bacterium (data are not showing in this paper).Keywords: virulence factors, MRSA, PVL, S.aureus, Nanoparticles.